PENGUJIAN MARSHALL CAMPURAN LASTON YANG MENGANDUNG BIOASPAL UNTUK LALU LINTAS SEDANG - , REZA ADHI KUSUMA, Dr. Eng., Iman Haryanto, ST., MT. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Asphalt is petroleum processed as petroleum feedstock which is good for the manufacture of asphalt is petroleum which contains asphalt (asphaltene) and contains little paraffin.In general, the use of asphalt is produced by artificial asphalt PT.Pertamina.The reduction in raw material (crude oil) and production costs tend to be expensive to make an excuse to produce bitumen from other raw materials are cheaper and more efficient. The idea arose from the existence of an idea to make the bitumen from oil palm shell raw material called bio asphalt. The initial process begins with the manufacture of bio-asphalt pyrolysis process to get the tar and oil palm shell liquid smoke.After the results obtained from the pyrolysis process, is the process of distillation to vaporize the liquid smoke and get the residue (bio asphalt).Bio asphalt that has been obtained is then mixed with bitumen oil from Pertamina. Bio bitumen asphalt mixing the oil is 1% - 10% of the weight of asphalt oil to be tested. Tests performed include: penetration testing asphalt, asphalt density testing, testing softening point, and ductility testing, and testing to see how mixing marshall maximum bio bitumen asphalt into oil. as well as to be able to know the levels of asphalt plans. After is done several testing above obtained the result of mixing maximum between bitumen oil and bio asphalt that fulfills the requirements is 99 % of oil and 1 % bio asphalt. As well as the values obtained bitumen content plan that is 7%. Further testing marshall with a mixture of aggregate used is asphalt concrete (LASTON) to obtain marshall quotient (MQ). From the test results can be obtained marshall MQ value: 485.5415 kg / mm. While the minimum limit MQ (marshall quotient) to laston is 200 kg / mm, so it can be concluded that the sempel testing meets the requirements and do not need further testing.